YURISDIKSI MENGADILI PELAKU PEMBAJAKAN PESAWAT UDARA BERDASARKAN PRINSIP MANDATORY EXTRADITION - Nur Aripkah (Fakultas Hukum Universitas Riau, 2020)
Extradition is basically a form of international cooperation to arrest or hand over a fugitive, suspect, defendant or convict who escape to another country. Extradition is based on agreements between countries to deal with crime. Mandatory extradition in The Hague Convention 1970 of 1970 certainly caused another debate, which in general we know that extradition is an agreement made between countries, and sometimes a country also does not want to make an extradition treaty with another country. However, with this principle that the member countries of the convention without exception are required to conduct extradition of the perpetrators of aircraft hijacking. The research method used is normative with the statues approach and conceptual approach. In the research it was found that the 1970 The Hague Convention was likened to a multilateral extradition treaty for convention participating countries. The principle of mandatory extradition stipulates extradition to be an obligation that must be carried out by each participating country of the convention as a step to tackle and try airplane hijackers.